KONSEP AL-UKHUWAH DALAM AL-QUR'`ĀN: KAJIAN TAFSIR TEMATIK - Ainul Churria Almalachim; Asep Maulana (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2019)
One of the important teachings that many of the Al-Qur'ān convey is about ukhuwah, and in Indonesian it is known as the teachings of brotherhood. The principle of al-ukhuwah contained in the Al-Qur'ān has been practised since the Al-Qur'ān was revealed, and the results were evident when the Prophet SAW built the city of Medina which was marked by the provisions of the Medina Charter. In this regard, it is understood that al-ukhuwah for every human being must be well-established, and with that al-ukhuwah it can unite them, and make their lives tolerant among others, tolerant between fellow Muslims as well as tolerant between Muslims and non-Muslims. This paper describes the concept of AlUkhuwah in the Al-Qur'an which is a thematic interpretation study.